2019
DOI: 10.1055/s-0039-1678674
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in the Diagnosis of CRPS after Open and Endoscopic Carpal Tunnel Release

Abstract: Background Complex regional pain syndrome (CRPS) occurs in 2 to 8% of patients that receive open or endoscopic carpal tunnel release (CTR). Because CRPS is difficult to treat after onset, identifying risk factors can inform prevention. We determined the incidence of CRPS following open and endoscopic CTR using a national claims database. We also examined whether psychosocial conditions were associated with CRPS after CTR. Methods We accessed insurance claims using diagnostic and procedural codes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
3
2
Order By: Relevance
“…This finding may support the use of perioperative antibiotic prophylaxis in this cohort. Previous studies have reported post-CTR CRPS rates of between 2% and 8%, 12,30-32 which is significantly higher than our finding of 0.21%; it is important to note that, however, some of the randomized controlled studies used comparatively smaller sample sizes of often less than 200 patients. Wound breakdown/dehiscence rates in our study (0.43%) were similar to previous estimates in the literature of 0.2%.…”
Section: Discussioncontrasting
confidence: 90%
“…This finding may support the use of perioperative antibiotic prophylaxis in this cohort. Previous studies have reported post-CTR CRPS rates of between 2% and 8%, 12,30-32 which is significantly higher than our finding of 0.21%; it is important to note that, however, some of the randomized controlled studies used comparatively smaller sample sizes of often less than 200 patients. Wound breakdown/dehiscence rates in our study (0.43%) were similar to previous estimates in the literature of 0.2%.…”
Section: Discussioncontrasting
confidence: 90%
“…Previous studies reported that the individual factors related to CRPS were age (23), female sex (10,24), preoperative pain (25), preoperative contracture (3), and fracture (6). In our investigation, none of these factors was statistically significantly different between groups U and N. Further, although the odds ratio for developing UDFS was extremely high in patients with fractures, no significant difference was found in logistic regression analysis, probably because the sample size was too small.…”
Section: Discussioncontrasting
confidence: 66%
“…Regarding the pathophysiology of CRPS, Groeneweg et al reported that endothelial damage caused by surgical incision triggers vasoconstriction that induces CRPS (7,8). On the other hand, Mertz et al reported no significant difference in the incidence rate of CRPS between endoscopic and open release procedures for carpal tunnel release (24). In their retrospective cohort study on distal radial fractures, Wang et al reported that use of a volar locking plate lowered the incidence rate of CRPS as compared with external fixation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Extremity injuries, such as fractures or sprains, surgery, and carpal tunnel syndrome have been the most commonly reported inciting events leading to CRPS [1][2][3]15]. In a recent analysis of 1043 patients with CRPS, the most common primary causes were fractures (42%), blunt traumatic injuries excluding fractures (e.g., sprains) (21%), surgery (12%), and carpal tunnel syndrome (7%), while 7% had no clear precipitating event [1].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Complex regional pain syndrome (CRPS) is a chronic pain condition characterized by hyperalgesia and allodynia, commonly involving the limbs. It frequently develops after extremity trauma or surgery [1][2][3]. The pathophysiology underlying the development of CRPS is still being explored, but the disorder is believed to result from central and peripheral nervous system dysfunction [4].…”
Section: Introductionmentioning
confidence: 99%